1995
DOI: 10.1902/jop.1995.66.5.403
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Studies on a Patient With Early Onset Periodontitis and Her Family Members. A Case Report

Abstract: Extensive clinical, microbiological, hematological, and immunological studies were performed on a patient with early onset periodontitis (EOP) and two other members of the family. The proband, a 27‐year‐old female, had early onset periodontitis and a high level of serum rheumatoid factors (RF) with no diagnosable medical disease. Her mother had lost all her teeth at the age of 50 because of advanced periodontitis, while her elder sister was unaffected by periodontitis. Neither the proband's periodontally‐affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…There are several other interesting reports on microbiological agents and lymphocyte dysfunctions that should be considered in relation to the progression of periodontal disease (2, 85). Takahashi et al (85) found high antibody titers to A. actinomycetemcomitans, P. gingivalis and C. rectus in the serum of the proband. High serum antibody titers to P. gingivalis were found in the mother, and to C. rectus in the unaffected sister, compared with the healthy control patients.…”
Section: Clinical Microbiological and Immunological Studies Of Familmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several other interesting reports on microbiological agents and lymphocyte dysfunctions that should be considered in relation to the progression of periodontal disease (2, 85). Takahashi et al (85) found high antibody titers to A. actinomycetemcomitans, P. gingivalis and C. rectus in the serum of the proband. High serum antibody titers to P. gingivalis were found in the mother, and to C. rectus in the unaffected sister, compared with the healthy control patients.…”
Section: Clinical Microbiological and Immunological Studies Of Familmentioning
confidence: 99%
“…There are several other interesting reports on microbiological agents and lymphocyte dysfunctions that should be considered in relation to the progression of periodontal disease (2, 85). Takahashi et al.…”
Section: Clinical Microbiological and Immunological Studies Of Familmentioning
confidence: 99%
See 1 more Smart Citation
“…Although fewer in number, subpopulations of T‐cells have also been investigated in patients with aggressive periodontitis . The presence of interleukin‐2, interferon gamma, interleukin‐4, interleukin‐5, interleukin‐10, interleukin‐13 and transforming growth factor beta was analyzed in CD3 + , CD4 + and CD8 + subpopulations extracted from gingival biopsies of healthy subjects, patients with gingivitis and patients with aggressive periodontitis .…”
Section: Role Of T‐helper‐cell Subsets In Periodontitismentioning
confidence: 99%
“…9,10 In fact, the majority of previous studies have shown that alteration in the host defensive cell functions, immunological and immunogenetic characteristics, such as neutrophil and lymphocyte dysfunctions, aberrant cytokine production and specific HLA types, are associated with the pathogenesis of some, but not all, EOP patients. 5,[11][12][13][14][15] Previous studies showing a high prevalence of EOP in certain families, [16][17][18][19] twin studies, 20 and the linkage with specific HLA types [21][22][23] suggest that susceptibility to this disease is heritable and that certain genetic risk factors may be involved. 24 Therefore, we have hypothesized that the heterogeneous nature of EOP could be explained from various host risk factors.…”
mentioning
confidence: 99%